Eğitim fakülteleri müzik eğitimi bölümlerinde eğitim almakta olan flüt öğrencilerinin profili - Sevim, Seda (My University, 2008)
Bu araştırmada Eğitim fakülteleri müzik eğitimi güzel sanatlar eğitimi bölümü anabilim dallarında bireysel çalgı-flüt eğitimi almakta olan öğrencilerin profili incelenerek flüt eğitimine başlama durumları saptanmıştır. Araştırmanın ilk aşamasında 56 sorudan oluşan bir anket çalışması yapılmıştır. Mezun olunan okul türü, müzik eğitimleri süresince bir okul çalgısı çalıp çalmadıkları, ilköğretim ve ortaöğretim öğrenimleri süresince hangi çalgıları çaldıkları, hangi seviyede çalıyor oldukları, kaç senedir çalıyor oldukları, müziğe başlama yaşları, nasıl müzik eğitimi aldıkları (kurs,özel ders), flüt eğitimine başlama yaşları, nasıl flüt eğitimine başladıkları, ailelerinde müziğe ilgili kişiler olup olmadığı, müzik dinleme alışkanlıkları, müzik kültürleri tespit edilmiştir. Hazırlanan anket öğrencilerin flütle ilgili bilgilerini ölçmek amacıyla Flüt Bilgi Testi ile devam etmiştir.

In this research, examining the profiles of flute students in Education Faculty – Music Education Department, their conditions at the beginning of their education lives are determined. Influence of instrument training prior to university education on election of students for instrument education in flute area of Education Faculty – Music Education Department has been observed. A survey based on Scanning Model has been applied to determine the reflection of a priori training to the success levels of students during their flute education in university. As the first step of the research, a survey of 56 questions has been accomplished. With the aid of this survey, information such as type of the graduated school, whether an instrument was used during musical education and sort of instruments that were played, type of education (private classes, courses), level of proficiency, years of education, whether there is an interest to music in their families, habit of listening to music and their music culture was gathered. The survey prepared has been followed by a Flute Knowledge Test that aims to measure the knowledge of students about flute.
Keywords: Eğitim_Müzik; Flüt_Müzik Aletleri; Müzik Eğitimi